The adenovirus-2 EIIa early gene promoter: sequences required for efficient in vitro and in vivo transcription. - Elkaim, R; Goding, C; Kédinger, C (1983)
A series of deletion mutants extending from -250 toward the capsite has been constructed in the early promoter region of the adenovirus 2 EIIa gene and tested both in vitro, and in vivo after transfection of HeLa cells, for the ability to act as a template for transcription. A region between positions -94 and -63 upstream from the major EIIa early cap site is essential both in vivo and in vitro for efficient promoter function. By cotransfection of the EIIa deletion mutants with the EIa transcription unit it has been possible to demonstrate that deletion to position -94 does not affect induction of transcription of the EIIa early gene by the EIa transcription unit, but deletion to position -63 results in loss of detectable levels of EIIa early specific RNA. Thus, sequences upstream from position -94 of the EIIa early gene are not involved in the induction of the EIIa early gene by the EIa transcription unit.